2015
DOI: 10.1021/acs.jnatprod.5b00581
|View full text |Cite
|
Sign up to set email alerts
|

Rotenoids, Flavonoids, and Chalcones from the Root Bark of Millettia usaramensis

Abstract: Five new compounds, 4-O-geranylisoliquiritigenin (1), 12-dihydrousararotenoid B (2), 12-dihydrousararotenoid C (3), 4'-O-geranyl-7-hydroxyflavanone (4), and 4'-O-geranyl-7-hydroxydihydroflavanol (5), along with 12 known natural products (6-17) were isolated from the CH2Cl2/MeOH (1:1) extract of the root bark of Millettia usaramensis ssp. usaramensis by chromatographic separation. The purified metabolites were identified by NMR spectroscopic and mass spectrometric analyses, whereas their absolute configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Phytochemical studies with Millettia species revealed that these species have a rich source of flavonoids, including isoflavonoids, rotenoids, chalcones, and pterocarpans [11,12]. M. ferruginea (Hochst) Baker, is an endemic of Ethiopia and has two representative species; ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies with Millettia species revealed that these species have a rich source of flavonoids, including isoflavonoids, rotenoids, chalcones, and pterocarpans [11,12]. M. ferruginea (Hochst) Baker, is an endemic of Ethiopia and has two representative species; ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, compounds previously isolated using chromatographic instrumentation can be studied offline using suitable methodologies. Among these are the conventional usage of ECD and polarimetric measurements , chemical correlation , diasteromeric NMR analysis , X‐ray diffraction analysis , when one is lucky and obtains crystalline samples, and VCD []. The later technique has shown many advantages for the stereochemical analysis of natural substances since it can be applied in the solution state with the use of rather inexpensive computational calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the indigenous people use aerial parts of Millettia plants as fishing poison and protecting stored food-grains from insects, which appear to be compatible with the typical presence of rotenoid compounds found in M. ferruginea and other species [3]. Most of the published literature on Millettia involved phytochemical analysis of the plant samples and this genus was found to contain a rich variety of structurally distinct isoflavonoids [5,15,23,24]. Unfortunately, these compounds have not been studied adequately regarding their prospective pharmacological properties.…”
Section: Discussionmentioning
confidence: 99%
“…contains various phenolic compounds belonging to the groups of flavonoids, alkaloids, rotenoids, diterpenes and pterocarpans [5,15,23,24]. Initially, the isoflavonoid durmillone was isolated from the seeds of Millettia dura and M. ferruginea [4,27].…”
Section: Discussionmentioning
confidence: 99%